Penyuluhan Perawatan Kebersihan Diri Pada Keluarga ODGJ Di Ratu Samban Kota Bengkulu - Tri Utami Rusmawati; Epitamala Sari; Herni Rahmayani; Nur Okta; Meilani Nanda Kartika; Yadi Ananda; Ade Herman Surya Direja (Pusat Riset dan Inovasi Nasional, 2023)
Mental disorders are one of the health problems that arise due to changes in the ability to think or behave due to disturbances in a person's psychological, biological, social, genetic and physical functions. The method we use is by conducting outreach. To increase understanding and the role of families in carrying out hygiene care, it is necessary to increase education in the form of counseling about strategies and tactics for maintaining cleanliness and appearance for family members who experience mental disorders. The aim of this outreach activity is to provide understanding as well as train families in carrying out care and teach patients to carry out daily activities and exercises such as: bathing, dressing, combing hair, cutting nails and washing hands independently. The aim of this outreach activity is to provide understanding as well as train families in carrying out care and teach patients to carry out daily activities independently.